The Influence of Influencer Authenticity and Electronic Word of Mouth (E-WOM) on Brand Trust: Empirical Evidence from N-Pure Skincare Consumers - Elis Nur Haliza; Siska Ernawati Fatimah (Journal Research of Social Science, Economics, and Management, 2026)
This study examined the influence of influencer authenticity and electronic word-of-mouth (e-WOM) on brand trust in the context of N’Pure skincare consumers in Indonesia. The increasing dominance of digital marketing has transformed how consumers evaluate brands, with trust increasingly shaped by social media interactions and influencer communication. However, issues such as fake reviews, paid endorsements, and a lack of transparency have raised concerns regarding declining consumer trust. The objective of this research was to analyze the effect of influencer authenticity and e-WOM on brand trust. A quantitative approach was employed using a survey method, with data collected from 180 respondents selected through purposive sampling. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software to test the proposed hypotheses. The results indicated that both influencer authenticity and electronic word-of-mouth had a positive and significant effect on brand trust. Influencers perceived as honest, consistent, and transparent were more likely to increase consumer confidence in a brand. Similarly, positive and credible e-WOM strengthened consumer trust through shared experiences and recommendations. In conclusion, influencer authenticity and e-WOM play crucial roles in shaping brand trust. This study highlights the importance of selecting credible influencers and managing online consumer feedback to strengthen the effectiveness of digital marketing strategies.